The grammaticalization and grammatical meaning of a ‘do’ support verb in the northern Italian Camuno dialect - Swinburne, N (De Gruyter, 2024)
This paper provides a case study of the grammaticalization of ‘do’ as a support verb in the northern Italian dialect of Camuno. It demonstrates the relative compatibility of fa ‘do’ with different semantic types of supported verbs through the results of an elicitation experiment. A comparison of results from adjacent dialects reveals a series of progressively more grammaticalized forms with three stages: ‘pragmatic’ ‘do’-support, largely restricted to agentive-subject, activity verbs, where question type depends mainly on the pragmatics; ‘agentive’ ‘do’-support, where use with that core group of verbs is largely categorial, and there is more use with theme-subject, change-of-state verbs and a few experiencer-subject, stative verbs; and ‘generalized’ ‘do’-support where optionality remains only with the most resistant stative verbs. Along with loss of lexical content in ‘do’, comes a reduction in salience of the special question meaning. Furthermore, a question with lexical fa ‘do’ (in an optional FS dialect) implies physical evidence exists to determine the truth of a proposition. In a question with bleached fa ‘do’ (in an obligatory FS dialect) the connection to reality has been lost leaving only the implication, and fa ‘do’ has then become an epistemic modal.